Amerindian ancestry proportion as a risk factor for inflammatory bowel diseases: results from a Latin American Andean cohort - Pérez-Jeldres, Tamara; Magne, Fabien; Ascui, Gabriel; Alvares, Danilo; Orellana, Matias; Alvarez-Lobos, Manuel; Hernandez-Rocha, Cristian; Azocar, Lorena; Aguilar, Nataly; Espino, Alberto; Estela, Ricardo; Escobar, Sergio; et al. (Frontiers in Medicine, 2023)
Background and aims. Latin American populations remain underrepresented in genetic studies of Inflammatory Bowel Diseases (IBD). Most genetic association studies of IBD rely on Caucasian, African, and Asian individuals. These associations have yet to be evaluated in detail in the Andean region of South America. We explored the contribution of IBD-reported genetic risk variants in a Chilean cohort and the ancestry contribution to IBD in this cohort. Methods. 192 Chilean IBD patients were genotyped using Illumina's Global Screening Array. Genotype data were combined with similar information from 3147 Chilean controls. Proportions of Aymara, African, European, and Mapuche ancestry were estimated using the software ADMIXTURE. We calculated the odds ratios (OR) and 95% confidence intervals (CI) for gender, as well as age and ancestry proportions. We also explored associations with previously reported IBD-risk variants independently and in conjunction with genetic ancestry. Results. The first and third quartiles of the proportion of Mapuche ancestry in IBD patients were 24.7% and 34.2%, respectively, and the corresponding OR was 2.30 (95%CI 1.52-3.48) for the lowest versus the highest group. Only one variant (rs7210086) of the 180 reported IBD-risk SNPs was associated with IBD risk in the Chilean cohort (adjusted p-value= 0.01). This variant is related to myeloid cells. Conclusion. The type and proportion of Native American ancestry in Chileans seem to be associated with IBD risk. Variants associated with IBD risk in this Andean region was related to myeloid cells and the innate immune response.